Karakteristik Fisik Kue Kembang Goyang dengan Substitusi Jewawut (Setaria italica L. P. Beauv.) dan Variasi Konsentrasi Santan - Anugrahati, Nuri A; Naomi, Jane (Universitas Pattimura, 2021)
â€œKue kembang goyangâ€ is a popular Indonesian traditional food made from rice flour. Millet flour with an amylose content equal to rice flour can be substituted for rice flour in the â€œkue kembang goyangâ€ formulation. The research aimed to determine the amylose content of 3 varieties of foxtail millet flour (Setaria italica (L.) P. Beauv.) and to determine the best formula of â€œkue kembang goyangâ€ in several ratios of foxtail millet flour:rice flour-based on crunchiness and oil absorption. The research was divided into two phases. Phase I, involved determining the amylose content of the three varieties of foxtail millet flour (erecta, compacta, glabra) and stage II involved determining the physical characteristics of â€œkue kembang goyangâ€ in the ratio of foxtail millet flour:rice flour (0: 100, 20:80, 40:60, 60:40, 80:20) and concentration of coconut milk (20%, 30%, 40%). The result of phase I showed that the highest amylose content was found in foxtail millet flour of erecta variety (37.91 Â± 0.51%). The phase II result showed that the ratio of foxtail millet flour:rice flour affected the texture and absorption of oil of â€œkue kembang goyangâ€. The higher the ratio of foxtail millet flour, the lower the count peaks, toughness, oil absorption, but the higher fracturability of â€œkue kembang goyangâ€. Increasing the concentration of coconut milk can increase count peaks, toughness, fracturability, and an oil absorption of â€œkue kembang goyangâ€. The best formula of â€œkue kembang goyangâ€ was obtained in the ratio of foxtail millet flour:rice flour 60:40 and 30 % of coconut milk-based on the highest crunchiness and oil absorption resembled the control. Keywords: Coconut milk; foxtail millet; â€œkue kembang goyangâ€; physical characteristics ABSTRAK Kue kembang goyang merupakan kue tradisional Indonesia yang popular dan terbuat dari tepung beras. Tepung beras dalam formula kue kembang goyang dapat diganti tepung jewawut yang memiliki kadar amilosa menyamai tepung beras. Tujuan penelitian adalah menentukan kadar amilosa tiga varietas tepung jewawut (Setaria italica (L.) P. Beauv.) dan menentukan formula terbaik kue kembang goyang pada beberapa rasio tepung jewawut:tepung beras berdasarkan kerenyahan dan absorpsi minyak. Penelitian dibagi menjadi tahap I yaitu menentukan kadar amilosa ke-3 varietas jewawut (erecta, compacta, glabra) dan tahap II yaitu menentukan karakteristik fisik kue kembang goyang pada rasio tepung jewawut:tepung beras (0:100, 20:80, 40:60, 60:40, 80:20) dan konsentrasi santan (20, 30, 40%). Hasil penelitian tahap I menunjukkan kadar amilosa tertinggi pada tepung jewawut varietas erecta (37,91 Â± 0,51%). Hasil penelitian tahap II menunjukkan rasio tepung jewawut:tepung beras berpengaruh terhadap tekstur dan absorpsi minyak kue kembang goyang. Semakin tinggi rasio tepung jewawut dapat menurunkan count peaks, toughness, absorpsi minyak, namun meningkatkan daya patah kue kembang goyang. Peningkatan konsentrasi santan dapat meningkatkan count peaks, toughness, daya patah, dan absorpsi minyak kue kembang goyang. Formula terbaik kue kembang goyang diperoleh pada rasio tepung jewawut:tepung beras 60:40 dan konsentrasi santan 30% berdasarkan kerenyahan tertinggi dan absorpsi minyak yang menyerupai kontrol. Kata kunci: Karakteristik fisik; kue kembang goyang; jewawut; santan